WISATA HUTAN DI DESA DAYAK KANAYATN - Canggita Lusya; Sutarki Sutisna (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
Deforestation is no stranger to people in West Kalimantan and even often becomes the center of national and world attention, one of which is the Kuburaya Regency, Sungai Ambawang District. Due to the function of the area as an area that produces forest products. The lives of local people are still very dependent on the forest, where the Dayak community has a holistic perception of the forest. For them, the forest does not only mean economic but also socio-cultural and religious. The very high rate of forest deforestation causes nature and culture in local communities to be marginalized due to the inability of culture to adapt to changes in regional conditions (with loss of forest cover/deforestation), so this research was carried out by applying cultural empowerment, namely, by strengthening cultural ecotourism in the local area and creating Past life, which can remind the Kanayatn Dayak culture to the younger generation in Korek Village, is very necessary, through a study of the Kanayatn Dayak typology approach, the rhymes of the jonggan dance songs and the settlement patterns of Korek Village and forest tourism telling the meaning of the jungle for the Dayak community which is very valuable. important for their daily activities. Served as the basic design in forming zoning, circulation patterns, building orientation, and building form. The design of this project uses a qualitative method with case studies and Kengo Kuma's design methods. The results of the research are the design of the Kanayatn Dayak cultural ecotourism with the application of the aspect of beyond ecology, which can increase the involvement of local communities in optimizing the program of conservation of natural resources and culture.Keywords:  Culture; Dayak Kanayatn; ecology; forest; tour.  Abstrak Deforestasi sudah tidak asing lagi didengar oleh masyarakat di Kalimantan Barat, bahkan sering menjadi pusat perhatian nasional dan dunia, salah satunya wilayah Kabupaten Kuburaya Kecamatan Sungai Ambawang. Dikarenakan fungsi daerahnya sebagai kawasan yang memproduksi hasil hutan. Kehidupan masyarakat lokal masih sangat bergantung pada hutan, dimana masyarakat dayak memiliki persepsi holistik terhadap hutan. Bagi mereka, hutan tidak hanya bermakna ekonomi melainkan juga sosio budaya dan religious. Tingkat deforestasi hutan yang sangat tinggi menyebabkan alam dan budaya pada masyarakat lokal mulai terpinggirkan akibat tidak mampunya budaya beradaptasi dengan perubahan kondisi kawasan (dengan hilangnya tutupan hutan / deforestasi), sehingga penelitian ini dilakukan penerapan pemberdayaan budaya yaitu, dengan memperkuat ekowisata budaya didaerah setempat dan menciptakan kehidupan masa lampau, yang dapat mengingatkan kembali budaya Dayak Kanayatn pada generasi muda di Desa Korek sangat diperlukan, melalui studi pendekatan tipologi Dayak Kanayatn, pantun syair lagu tarian jonggan dan pola pemukiman Desa Korek dan wisata hutan mengisahkan makna hutan rimba bagi masyarakat dayak yang bernilai sangat penting bagi kehidupan aktivitas sehari – hari mereka. Dijadikan sebagai desain dasar dalam membentuk zoning, pola sirkulasi, orientasi bangunan, dan bentuk bangunan. Desain proyek ini menggunakan metode kualitatif dengan studi kasus dan metode design milik Kengo Kuma. Hasil penelitian berupa desain ekowisata budaya Dayak Kanayatn dengan penerapan aspek beyond ecology, yang dapat meningkatkan keterlibatan masyarakat lokal dalam mengoptimalkan program kegiatan pelestarian SDA dan budaya.